Development of the Malaysian Orang Asli coping strategy scale to measure household food insecurity among the Orang Asli - Law, Leh Shii (2018)
Indigenous People in Peninsular Malaysia is known as Orang Asli (OA), a marginalized group due to high poverty rate. Unsurprisingly, studies showed that OA were severely burdened with household food insecurity. Most forms of indirect and direct measures used to back up years of food insecurity research lacked sensitivity and specificity. Upon seeing potentials for a new conceptual framework to be made from this weakness, this study aimed to develop a household food insecurity measuring-instrument for the OA in Peninsular Malaysia. This study was divided into two parts, namely Phase I and Phase II. In Phase I, a case study design (qualitative research) was applied. Through in-depth interviews, relevant information related to the household food insecurity experience of OA (particularly coping strategies) was gathered from 61 Senoi, Proto-Malay, and Negrito women in Pahang, Kelantan, and Perak. Next, the severity level of household food insecurity for coping strategies were determined through focus group discussions among 19 Proto- Malay women in Selangor. Based on the given information, a list of items for the development of the Malaysian Orang Asli Coping Strategy (MORACS) Scale were prepared. The content validity of the items were evaluated by experts. In Phase II, a cross-sectional study design was applied. The purpose of conducting Phase II was to evaluate the validity and reliability of the newly developed MORACS Scale, with the help of 355 Senoi women in 19 randomly selected villages at Batang Padang District, Perak. The exploratory factor analysis (EFA) was performed to validate the construction of the MORACS Scale, followed by the Rasch analysis. The internal consistency and test-retest reliability of the MORACS Scale were thoroughly investigated, before the validity criterion of the MORACS Scale could be evaluated by using several indirect measures, namely demographic and socioeconomic characteristics, dietary intakes, anthropometric measurements, and quality of life. Statistical tests such as independent samples t-test, analysis of variance (ANOVA), and general linear model (GLM) were applied. In Phase I, twenty-nine food consumption (19 items) and financial management (10 items) coping strategies were identified, based on the severity level of household food insecurity; ‘less severe’, ‘severe’, or ‘very severe’. By the end of Phase II, the refined MORACS Scale had 14 food consumption coping strategies. All the items appeared to be unidimensional under the Rasch analysis (explained 64.6% variance), despite the EFA indicating four factors to the items (explained 57.1% variance). In addition, the internal consistency and test-retest reliability for the MORACS Scale was good (Cronbach’s alpha: 0.763; correlation: r = 0.492, p < 0.001). The criterion validity of the MORACS Scale was appropriate as well, based on the significant differences (p < 0.05) in the mean MORACS score among respondents with distinct demographic and socioeconomic characteristics, together with the significant differences (p < 0.05) in the adjusted means of dietary intakes among three household food security statuses.